2022
DOI: 10.1177/21582440211071102
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Approach to Air Passenger Index Prediction: Based on Mutual Information Principle and Support Vector Regression Blended Model

Abstract: Air passenger traffic prediction is crucial for the effective operation of civil aviation airports. Despite some progress in this field, the prediction accuracy and methods need further improvement. This paper proposes an integrated approach to the prediction of air passenger index as follows. Firstly, the air passenger index is defined and classified by the K-means clustering method. And then, based on mutual information (MI) principle, the information entropy is used to analyze and select the key influencing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…This is necessary to create a strategy for the airports operation with a satisfactory level of passenger service quality and the organization of operational activities of transport means. Similar questions and approaches to their solution have already been covered in the works of contemporaries [430][431][432][433]. The authors of the paper [433] proposed an approach to determine the airport capacity and passenger flow fluctuations using the air passenger index introduced by them.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…This is necessary to create a strategy for the airports operation with a satisfactory level of passenger service quality and the organization of operational activities of transport means. Similar questions and approaches to their solution have already been covered in the works of contemporaries [430][431][432][433]. The authors of the paper [433] proposed an approach to determine the airport capacity and passenger flow fluctuations using the air passenger index introduced by them.…”
mentioning
confidence: 89%
“…Similar questions and approaches to their solution have already been covered in the works of contemporaries [430][431][432][433]. The authors of the paper [433] proposed an approach to determine the airport capacity and passenger flow fluctuations using the air passenger index introduced by them.…”
mentioning
confidence: 89%
“…Deep learning is computationally very complex, showing the model's tendency to overfit. A recent study found that hybrid models worked well and attempted to combine the best features of various models [115]. Complex deep neural networks are the future when time-series data contain uncertainty.…”
Section: Hybrid Modelsmentioning
confidence: 99%
“…The global “digital divide” status quo is quickly changing with the progress in artificial intelligence (AI) technologies and their application area expansion. Nowadays, AI has been widely researched and achieves great success in recent years, and the heart of AI technologies is machine learning (ML) algorithms ( Xiong et al, 2022 ). With the development of the digital economy, Internet, Internet of things (IoT), mobile Internet, and cloud technologies, the application of AI based on health big data presents an explosive increase in recent years ( Gokmen and Vlasov, 2016 ; Dolley, 2018 ; Ngiam and Khor, 2019 ; Ye et al, 2021 ; Weerasinghe et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%